Специфіка семантичних процесів в українській науково-технічній термінології - Кримець, Оксана Михайлівна (Харківський національний педагогічний університет ім. Г. С. Сковороди, 2020)
У статті досліджено семантичні процеси як чинники розвитку термінологічної лексики. Розглянуто специфіку таких семантичних процесів, як розширення, звуження й зміщення значення у сфері української науково-технічної термінології. На численних прикладах продемонстровано, що семантичний процес розширення значення в термінології супроводжується детермінізацією й ретермінізацією, процес звуження значення – термінізацією й ретермінізацією, а процес зміщення – термінізацією, ретермінізацією й транстермінізацією. Доведено, що мотивують семантичні процеси в термінології метафоричне переосмислення й метонімне зрушення вихідних значень.

The topicality of the research lies in the study of semantic processes as factors in the development of terminological vocabulary and the analyses of changes that give rise to new meanings, which reflect the progressive development of science and technology and feature the principles of categorization of relevant fragments of objective reality in the semantic structure of special naming units. The purpose of the article is to determine the specificity of semantic processes in Ukrainian scientific and technical terminology. The task of the study is to characterize the semantic processes of extension, narrowing and shifting of the term and common word meanings, to determine the motivator of this process and the characteristics of semantic processes in the field of terminological vocabulary. The results of the research have shown that terms as well as common words have such semantic processes as extension, narrowing, and shifting of the meaning. The extension of the term causes a new, commonly used word (which could change the meaning of the word for better or worse) or a new term. When narrowing the meaning of the word, a commonly used word or term is reinterpreted with a broad meaning. The semantic process of the meaning shift is characteristic of both common and special names. These processes are motivated by the metaphorical reinterpretation that occurs on the basis of similarity of function or appearance, as well as metonymic shifts, in particular such models as “X – X where it is used”, “X – containing X”, “repository – content”, “science is the object matter”, “part – whole”, and others. Characteristic aspects of semantic processes in the field of Ukrainian scientific and technical terminology lie in the fact that the extension, narrowing or shift of the meaning, result in termination, determination, retermination, and transtermination of the original word. The emergence of a new terminological or common meaning is the result of these processes.
Characteristic Aspects of Semantic Processes in Ukrainian Scientific and Technical Terminology
Keywords: семантичні процеси; термінологія; метафори; метонімія; semantic processes; terminology; metaphoric expression; metonymy